Volume of Parenchyma and Non-parenchyma in Human Placenta in Gestational Diabetes and Eclampsia (IAHS Medical Journal, 2026)
Background: Eclampsia and gestational diabetes mellitus are metabolic conditions linked to pregnancy that have significant effects on the structure and function of the placenta. The goal of this study was to examine the relative and absolute volumes of the human placenta's parenchymal and non-parenchymal components in cases of eclampsia and gestational diabetes mellitus.Materials and methods: A total of sixty placentae from the control, gestational diabetes mellitus and eclampsia groups (n = 20 each) were analysed. The point counting approach was used to estimate the volume of placental components.Results: Without appreciable proportional alterations, placentae from gestational diabetes mellitus showed higher absolute volumes of both parenchyma and non-parenchyma. On the other hand, placentae from eclampsia displayed a proportionate rise in non-parenchymal components together with a considerable /significant decrease in absolute parenchymal volume.Conclusion: Different patterns of placental remodelling are seen in gestational diabetes mellitus and eclampsia, with the former showing primarily adaptive modifications and the latter showing pathogenic abnormalities.IAHS Medical Journal Vol 8(2), December 2025; 5-9